MECHANISM OF THE CASTING FORMING AT VERTICAL CONTINUOUS FOUNDING - E. B. Demchenko; E. I. Marukovich (Литьë и металлургия, 2006)
The mechanisms of the casting forming which consider the character of hardening of initial shell from the side of the cooling surface of the crystallizer of the system ''castingcrystallizer” are specified. It is shown that zones of forming determine the character and the field of hardening of the casting shell, and temporary stages of forming - the consequence of the shell hardening in these zones in time.